The history and applications of phage therapy in pseudomonas aeruginosa - Silva, Carina (2022)
The Pseudomonas aeruginosa is one of the bacteria that cause serious infections due to resistance to many antibiotics can be fatal in severe cases. Antimicrobial resistance is a global public health concern. To solve this problem, interest in phage therapy has revived; some studies are being developed to try to prove the effectiveness of this therapy. Thus, in this opinion article, several historical aspects are addressed as well some applications of phage therapy against P. aeruginosa.